Cultivation requirements and substrate degradation of the edible mushroom Gymnopilus pampeanus—A novel species for mushroom cultivation - Colavolpe, Maria Belen (2014)
The production of new species of edible mushrooms is an innovative way to recycle agro-industrial wastes into food production. The genus Gymnopilus has a large number of xylophagous species being Gymnopilus pampeanus the only consumed species. The objective of this work is to determine the optimal condition needed to cultivate G. pampeanus, to evaluate its biological efficiency and to determine the biodegradation of substrate. Populus and Eucalyptus sawdust were used as substrates for production. We determined that light is necessary for a normal development of primordia. Strain ICFC 748/12 produces the highest biological efficiency on Populus sawdust reaching a mean of 70.67%. G. pampeanus has a strong capacity to degrade Eucalyptus and Populus. This mushroom has the ability to decompose cellulose and also to decay lignin, thus being white rot fungi. This is the first report of the cultivation of this species on lignocellulosic waste which turns it into a promising species for commercial production.